(untitled) (Research, Society and Development, 2022)
Introduction: The growth of pharmacy networks and the installation of diverse stores in all the cities of the state of Paraná has made it difficult for independent commercial pharmacies to compete. Marketing is a set of techniques linked to the flow of goods and services covering decisions related to the use of prices, sales and investment of companies. Objective: Verify through a bibliographic review which Marketing strategies can contribute with independent pharmacies to increase customer loyalty and profitability. Methodology: The research used data obtained by academic sites such as: GOOGLE ACADÊMICO and SCIELO, considering the terms of search “marketing in drugstores” and “pharmaceutical retail”. Data published from 2000 to March 2022 were considered. Results: 2,345 articles were found in the database. Of these, 1,985 were articles that were incompatible with the purpose of the bibliographic review or had no associated outcomes related to the strategies of the independents pharmacies and 253 were duplicates. After reading the title and summary of these articles, 107 articles met the inclusion criteria and they were selected for a full reading. Of these, 8 (eight) studies were included for a data extraction. Conclusion: As independent pharmacies must focus on customer loyalty through pharmaceutical and commercial services, such as: measuring pressure, temperature, blood sugar, investment in clinical pharmacy services, deliveries, fast and effective communication methods.